A Biopolymer System for Cell Recovery from Microfluidic Cell Capture Devices - Shah, Ajay M. (2012)
Microfluidic systems for affinity-based cell isolation have emerged as a promising approach for the isolation of specific cells from complex matrices (i.e., circulating tumor cells in whole blood). However, these technologies remain limited by the lack of reliable methods for the innocuous recovery of surface captured cells. Here, we present a biofunctional sacrificial hydrogel coating for microfluidic chips that enables the highly efficient release of isolated cells (99% ± 1%) following gel dissolution. This covalently crosslinked alginate biopolymer system is stable in a wide variety of physiologic solutions (including EDTA treated whole blood) and may be rapidly degraded via backbone cleavage with alginate lyase. The capture and release of EpCAM expressing cancer cells using this approach was found to have no significant effect on cell viability or proliferative potential and recovered cells were demonstrated to be compatible with downstream immunostaining and FISH analysis.